2017
DOI: 10.1039/c7ra11014f
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar electronic, strong in-plane and out-of-plane second harmonic generation and piezoelectric properties of atom-thick α-M2X3 (M = Ga, In; X = S, Se): role of spontaneous electric dipole orientations

Abstract: Single- and few-layer α-M2X3 nanosheets exhibit out-of-plane SHG and piezoelectric properties, which can be tuned by switching spontaneous polarizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 53 publications
(89 reference statements)
6
50
0
1
Order By: Relevance
“…To be compatible with the nowadays bottom/top gate technologies, a large out-of-plane piezoelectric d 31 is highly desired for 2D materials. The d 31 of Janus monolayer Fe 2 IX (X=Cl and Br) is higher than ones of many 2D materials, like Janus TMD monolayers (0.03 pm/V) 6 , functionalized h-BN (0.13 pm/V) 50 and kalium decorated graphene (0.3 pm/V) 51 , and is comparable with ones of the oxygen functionalized MXenes (0.40-0.78 pm/V) 15 , Janus group-III materials (0.46 pm/V) 52 , Janus BiTeI/SbTeI monolayer (0.37-0.66 pm/V) 53 and α-In 2 Se 3 (0.415 pm/V) 54 .…”
Section: Piezoelectric Propertiessupporting
confidence: 52%
“…To be compatible with the nowadays bottom/top gate technologies, a large out-of-plane piezoelectric d 31 is highly desired for 2D materials. The d 31 of Janus monolayer Fe 2 IX (X=Cl and Br) is higher than ones of many 2D materials, like Janus TMD monolayers (0.03 pm/V) 6 , functionalized h-BN (0.13 pm/V) 50 and kalium decorated graphene (0.3 pm/V) 51 , and is comparable with ones of the oxygen functionalized MXenes (0.40-0.78 pm/V) 15 , Janus group-III materials (0.46 pm/V) 52 , Janus BiTeI/SbTeI monolayer (0.37-0.66 pm/V) 53 and α-In 2 Se 3 (0.415 pm/V) 54 .…”
Section: Piezoelectric Propertiessupporting
confidence: 52%
“…6 Also, previous study suggested that Ga 2 X 3 and In 2 X 3 single layers are energetically favorable. 10 The cohesive energy E c of the Janus GaInX 3 single-layers can be evaluated by:…”
Section: Atomic Structure and Stabilitymentioning
confidence: 99%
“…Based on Equation 14, the calculated d 31 is -0.238 pm/V. The d 31 of Janus monolayer Li 2 Fe 2 SSe is higher than or comparable with ones of many 2D materials [59][60][61][62] . The Coulomb interaction U effects on piezoelectric properties of monolayer Li 2 Fe 2 SSe are also considered.…”
Section: Piezoelectric Propertiesmentioning
confidence: 99%